Plant Performance and Storability Tomato (Solanum lycopersicum L.) Fruit With theApplication of Calsium Chloride (CaCl2) - Faradilla, Nisa; Kurniadinata, Odit Ferry (Mulawarman University, 2025)
This study was conducted to determine the interaction of CaCl2 concentration and application technique on the tomato plant performance and storability of tomatoes. The CaCl2 concentration (K) consisting of k0 (0 mL L -1 ), k1 (0.5 mL L -1 ), k2 (1.0 mL L -1 ), k3 (1.5 mL L -1 ), k4 (2.0 mL L -1 ) and application technique (T) consisting of t1 (sprayed on the plant) and t2 ( watered into the growing media). The results shows that k2t2 combination obtained the maximum number of flowers with an average 24.33 florets and obtained height of tomato plant. The maximum number of fruits was obtained by k3t2 combination (11.33 florets), followed by k4t2 combination (11.00 florets). The minimum number of flowers fall off was obtained by k0t2 combination (1.00 florets) and the maximum number of flowers fall off was obtained by k3t1 combination (4.67 florets). The combination of k4t1 and k4t2 gave the best results on blossom endrot diseases (zero diseases) and storability of tomatoes (up to 30 days).